Handbook of childhood and adolescent obesity - Steele, Ric G. (Springer, 2017)
Within the past two generations alone, child and adolescent obesity has more than doubled for some age groups and tripled for others. Consequently, the extraordinary number of school-age children now being diagnosed with what were once considered adult-onset disorders – hypertension, type 2 diabetes, high cholesterol, and related cardio-pulmonary conditions – has catapulted pediatric obesity to the forefront of national attention. Yet even as recognition grows, reliable, scientifically tested information and methods often get lost in the media crush of quick fixes and hyped-up news stories.